1983
DOI: 10.1073/pnas.80.7.1951
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-thyroid synergism in lung maturation: a mechanism involving epithelial-mesenchymal interaction.

Abstract: We studied the effects of cortisol and triiodothyronine (T3) on 20-day fetal rat lung cell cultures. Cortisol -enhanced the production of surfactant-associated saturated phosphatidylcholine while T3 did not. However, T3 potentiated the cortisoleffect. We observed that T3 enhanced the response of cultures enriched-with alveolar type 11 cells to fibroblast-pneumonocyte factor (FPF). Intracellular cAMP was increased by exposure of these cultures to FPF, and T3 potentiated this increase. Unlike cortisol, T3 had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(25 citation statements)
references
References 17 publications
(22 reference statements)
1
24
0
Order By: Relevance
“…In addition, to determine whether DEX (which accelerates AOE development) would be able to reverse the effect of TRH (depression bf AOE development), we used combined drug therapy and found that although the addition of DEX to TRH resulted in a greater positive effect on surfactant system maturation (increased DSPC), combined DEX plus TRH treatment produced an enhanced negative effect on AOE system development, with further depression of CAT and G P activities in the late gestation fetal lung. This apparent inability of DEX to counteract TRH's depression of AOE system development might be explained if these two hormones act on different cell types or if both TRH and DEX act on the type I1 pneumocyte (the alveolar lining cell most resistant to hyperoxic exposure) (29,(40)(41)(42) but at different sites. It appears from the hormonal measurements in the present study that TRH is working through the secretion of T j and T4 rather than through the release of prolactin, which is consistent with studies previously reported by Klindt d al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to determine whether DEX (which accelerates AOE development) would be able to reverse the effect of TRH (depression bf AOE development), we used combined drug therapy and found that although the addition of DEX to TRH resulted in a greater positive effect on surfactant system maturation (increased DSPC), combined DEX plus TRH treatment produced an enhanced negative effect on AOE system development, with further depression of CAT and G P activities in the late gestation fetal lung. This apparent inability of DEX to counteract TRH's depression of AOE system development might be explained if these two hormones act on different cell types or if both TRH and DEX act on the type I1 pneumocyte (the alveolar lining cell most resistant to hyperoxic exposure) (29,(40)(41)(42) but at different sites. It appears from the hormonal measurements in the present study that TRH is working through the secretion of T j and T4 rather than through the release of prolactin, which is consistent with studies previously reported by Klindt d al.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, based on a variety of experimental (animal) evidence that thyroid hormone treatment combined with glucocorticoid treatment has an additive or synergistic effect on stimulating surfactant system development (21,22), combined hormonal therapy has been tested clinically. However, because the human placenta is rather impermeable to thyroid hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are involved in normal foetal development, with thyroid hormone status playing important roles in the development and function of other organs that originate from epithelial-mesenchyme interactions, such as the lungs (Smith and Sabry, 1983). The importance of thyroid hormones during foetal development was best described by Hopkins and Thorburn (1972), who performed foetal thyroidectomy between D81 and D96, resulting in increased gestation, lower BW and high perinatal mortality.…”
Section: Introductionmentioning
confidence: 99%